Psychological Factors and Their Relationship to Simultaneous Interpretation - Al-Maqtari, Amal Abdulwase'a Makrad Qaid et al. (University of Science and Technology, Sana'a, Faculty of Humanities and Social Sciences, Translation Program, 2025)
This study aims to investigate the impact of psychological factors, such as anxiety and stress, on the performance of simultaneous interpreters. Despite the common belief that high levels of anxiety and stress negatively affect interpreting performance, the findings of this research indicate otherwise. Data were collected from a sample of twenty-fourth-year translation students at the University of Science and Technology. To collect the data, the study utilized the State-Trait Anxiety Inventory (STAI) questionnaire, consisting of twenty items, and a two-minute and fifteen-second interpreting test. Moreover, the study followed a descriptive analysis method based on a qualitative and quantitative nature. The findings showed that all students passed the test, with the highest score being 10/10 (5%) and the lowest score being 5/10 (5%), while the scores of the remaining students varied between 8/10 (30%) and 7/10 (60%). The analysis revealed no significant correlation between anxiety and stress levels and the interpreters' performance. These results suggest that other factors, such as training, experience, and coping mechanisms, play a more critical role in determining interpreting proficiency. The study calls for a reevaluation of current training methods and emphasizes the need for further research to investigate additional elements that contribute to effective simultaneous interpretation.